Basin edge effect at Turkish basins: The case study of dinar and Duzce basins - Khanbabazadeh, Hadi; Iyisan, Recep; Haşal, Murat Emre; Zülfikar, Abdullah Can (National Technical University of Athens, 2019)
Several studies have revealed that the inclined bedrock at the sides of the basins bring about the concentration of damages, which well known as basin edge effect. As a seismically active area much of the Turkey lies on the Anatolian Plate. This small plate bounded by two major strike-slip fault zones, the North Anatolian Fault and East Anatolian Fault. During the history, Turkey has been the site of devastating earthquakes. Severe structural damage at basin sides during recent major earthquakes around the world strongly pointed out the importance of basin edge effect. Some of its notable examples can be tracked in Turkey. With respect to the fact that Turkey is among the top 20 percent of all countries exposed to earthquake hazard with regard to mortality and economic losses, the necessity of the investigation and consideration of the basin edge effect in earthquake design codes is revealed. In this study, the dynamic behavior at the edge of two real basins is investigated. In this study, at the first, the basin edge model of the basins are extracted from the data obtained from extensive microtremor surveys and geotechnical investigations as well as insitu studies including SPT, CPT, PS logging tests. Then, the idealized geometry of the Dinar and Duzce basins edge models are proposed. Afterwards, the basins are subjected to the collection of strong ground motions using a fully nonlinear method which works based on explicit finite difference scheme FLAC3D code. The idealized 2D model of the Dinar and Duzce basins are subjected to the collection of sixteen strong ground motions with different peak ground accelerations (PGA) level of 0.1, 0.2, 0.3 and 0.4 g, four motions for each PGA level. For missing the effect of soil layers on selected real accelerograms they have been chosen from among those recorded on stiff layers during real earthquakes, or deconvoluted to the corresponding bedrock motion. After the application of the strong ground motions from the bottom of the models in time domain, the acceleration of the surface points were recorded. For each surface point, the maximum spectral amplification factor under each earthquake is calculated then the average of resulted spectral amplification for four earthquakes of the same PGA level was estimated and reported. The results of the dynamic analysis of Duzce basin showed the dominant effect of the inclined bedrock at the basin edge. Also, variation of its effect under excitations with different PGA levels is evident. At this basin the highest amplification factor occurs under the motions with PGA of 0.2g. Also, unlike the rest of the curves, a de-amplification of 0.85 along about 200 meters from the basin edge occurred at Duzce basin edge which shows that the basin edge can sometimes have decreasing effect on amplification. Regarding the influenced distance by the basin edge, while this distance is bout 800m and 1000m for the motions with the PGA of 0.1g and 0.2g, it increases to 1250m and 1500m for the motions with the PGA of 0.3g and 0.4g, respectively. For asymmetric Dinar basin, two different amplification behaviors were seen at the eastern and western edges of the basin in terms of amplification amount and influenced distance by the basin edge. The higher basin edge effect at the eastern part with lower bedrock inclination with respect to western part was seen. This shows the higher effect of bedrock with lower angles. While the highest amplification factor at the western side occurs under the motions with PGA of 0.3g, it happens under the motions with PGA of 0.1g at the eastern side. Also, it was seen that at the eastern part of the basin has affected the distance about 1500 m from the outcrop while this distance for the steeper bedrock angle at the western side is about 700 m from outcrop. Between these distances 1D behavior is dominant. The results show that the dynamic behavior of the both Dinar and Duzce basins at their sides is under the effect of basin edge in terms of amplification amount and influenced distance by the basin edge. At the basin edges, comparable amplification amounts with respect to the inner parts of the basins were seen. © 2020 Elsevier B.V., All rights reserved.
7th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering, COMPDYN 2019 -- Crete -- 157145
Keywords: Basin edge effect; Dinar Basin; Duzce Basin; Dynamic behavior; Microtremor; Numerical modeling; Site effect